International Capital Markets, August 2001 - Mathieson, Donald (World Economic and Financial Surveys; World Economic and Financial Surveys, 2001)
This paper reports the on-off nature of emerging market access to international capital markets appears to have become a key characteristic of international financial markets. Emerging market borrowers have begun to adapt: when the market for US dollar-denominated bonds has closed, these borrowers turn to the syndicated loan markets, attempt to issue in bonds denominated in euro or yen, or issue in local-currency bond markets. In addition, they employ staff with extensive experience in investment banking and securities trading, exploit 'windows of opportunity' to prefund their yearly financing requirement, and engage in debt exchanges to extend the maturity of their debt and avoid a bunching of maturities. The consolidation of financial institutions is driven by attempts to exploit economies of scale and scope, and technological advances such as the Internet and deregulation that facilitate universal banking activities are making it easier to reap such economies. Advances in technology are also transforming the securities trading industry.